EVIRDB – A COMPREHENSIVE VIRULENCE FACTORS DATABASE OF ENTEROBACTERIACEAE - THIRUNAVUKKARASU MURUGESAN,; DINAKARAN KARUNAKARAN,; GNANENDRA SHANMUGAM, (International Journal of Pharma and Bio Sciences, 2015)
The continuous emergence of multidrug resistant bacteria has become a greater concern for the public health sectors. The knowledge on the mechanism of bacterial pathogenesis, surveillance in the host system and its resistance to antibiotics has attained a greater attention of researchers to understand the critical virulence factors of bacterial pathogens. The identification of novel virulence factors that can prioritize its importance as a drug target is most promising challenge of many pharmaceuticals. Thus the development of the virulence factor database as a specialized repository that can facilitate the researchers to quickly mine the virulence factors of specific bacteria has become necessary. Hence, in the present research, the database EVirDB (http://www.evirdb.info), presented as a source for the rapid access of different virulence factors based on the gene ontology terms. The EvirDB is designed as a comprehensive and user-friendly database. The database provides the users to submit the query and to retrieve the virulence factors data of bacterial pathogens that belong to Enterobacteriaceae.